Cytologic presentation of ovarian large cell carcinoma with rhabdoid features detected on peritoneal washing. Report of one case with cyto‐histologic correlation and previously undescribed inactivating SMARCA‐4 mutations. Issue 3 (14th December 2021) - Fulciniti, Franco; Barizzi, Jessica; Migliora, Paola; Papadia, Andrea; Mazzucchelli, Luca
Abstract: The SMARCA subgroup of genes belongs to the SWI1/SNF1 family, responsible for chromatin remodeling and repair within the nucleosome. The SMARCA4 gene is located on chromosome 19p13 and encodes the BRG1 (BRAhMA) protein. We report the cytological and histological findings in one case of large cell SMARCA4 deficient ovarian carcinoma with positive peritoneal washing in a 69‐year‐old woman. The neoplastic cells were present as singly lying or perivascular clusters and showed medium or large size, round to oval hyperchromatic nuclei, and scarce to moderate cytoplasms. Molecular pathology investigations performed on the ovarian surgical sample found two previously undescribed mutations in the SMARCA4 gene and additional mutations in the CTNNB1 (Beta Catenin gene) and in PIK3CA. To our knowledge, this case probably represents the third cytologic report of this variant of ovarian carcinoma and the first one with molecular pathologic study.